Elemental Analysis of Aging Human Pituitary Glands Implicates Mercury as a Contributor to the Somatopause - Pamphlett, Roger; Kum Jew, Stephen; Doble, Philip A.; Bishop, David P. (Frontiers in Endocrinology, 2019)
Background: Growth hormone levels often decline on aging, and this ‘somatopause’ is associated with muscle and bone loss, visceral adiposity and impaired cardiovascular function. Mercury has been detected in human pituitary glands, so to see if mercury could play a part in the somatopause we measured the proportion of people at different ages who had mercury in their anterior pituitary cells. Materials and methods: Paraffin sections of pituitary glands taken at autopsy from 94 people between the ages of 2 and 99 years were stained for inorganic mercury using autometallography. Pituitary mercury content was classified as none, low (<30% of cells) or high (>30% of cells) in increasing two-decade age groups. Autometallography combined with immunohistochemistry determined which hormone-producing cells contained mercury. Laser ablation-inductively coupled plasma-mass spectrometry was used to confirm the presence of mercury. Results: The proportion of people with low-content pituitary mercury remained between 33-42% at all ages. The proportion of people with high-content mercury increased with increasing age, from 0% of people in the 2-20 year group to a peak of 50% of people in the 61-80 year group, followed by a fall to 35% of people in the 81-99 year group. Mercury, when present, was found always in somatotrophs, occasionally in corticotrophs, rarely in thyrotrophs and gonadotrophs, and never in lactotrophs. Laser ablation-inductively coupled plasma-mass spectrometry detected mercury in regions of pituitaries that stained with autometallography. Conclusions: The proportion of people with mercury in their anterior pituitary cells, mostly somatotrophs, increases with aging, suggesting that mercury toxicity could be one factor contributing to the decline in growth hormone levels found in advancing age.